2021
DOI: 10.3389/fcvm.2021.644189
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes and Myocardial Infarction: Recent Clinical Evidence and Perspective

Abstract: Type 2 diabetes mellitus (T2DM) and its complications are seriously affecting public health worldwide. Myocardial infarction (MI) is the primary cause of death in patients with T2DM. T2DM patients without a history of coronary artery disease (CAD) have the same risk of major coronary events as those with CAD; T2DM patients with a history of MI have >40% risk of recurrence of MI. Thus, CAD in patients with T2DM needs to be treated actively to reduce the risk of MI. The cardiology community focused on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 53 publications
1
37
0
3
Order By: Relevance
“…Type 2 diabetes mellitus (T2DM) and myocardial infarction (MI) represent two major health burdens with steadily increasing prevalence and mortality. 13 T2DM is a chronic disorder that is characterized by hyperglycemia and insulin resistance. It has been recognized as an independent risk factor for cardiovascular disease including atherosclerosis, myocardial infarction, nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) and myocardial infarction (MI) represent two major health burdens with steadily increasing prevalence and mortality. 13 T2DM is a chronic disorder that is characterized by hyperglycemia and insulin resistance. It has been recognized as an independent risk factor for cardiovascular disease including atherosclerosis, myocardial infarction, nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, numerous clinical studies have confirmed that sodium-glucose cotransporter 2 (SGLT2) inhibitors and glucagon-like peptide 1 (GLP-1) receptor agonists reduce the risk of CVD, and their clinical indications have also been included in treatment guidelines ( 31 ). However, few studies have investigated the effects of hypoglycemic agents on depression and no guidelines are available.…”
Section: Treatmentmentioning
confidence: 99%
“…冠心病病证结合防治策略 虽然现代医学在冠心病的二级预防、经皮冠状动脉介入治疗(PCI) 、冠状 动脉旁路移植术(CABG)等防治手段上取得显著进展,然而目前临床仍然存 在不能有效阻断冠脉临界病变、介入术后胸痛症状缓解不明显,不能耐受二级 预防的药物治疗、抗血小板药物抵抗,无法血运重建的冠脉复杂病变、心梗后 心衰的防治手段匮乏等现代医学亟待解决的临床关键科学问题 [122] 。因此,开展 针对冠心病为核心的重大心血管疾病的中医药防治研究、降低患病率和死亡 率,业已成为国家重大的公共卫生需求。 病证结合的系统化研究为冠心病的疾病分类提供了中医视角,围绕冠心病 血瘀证的生物学实质的探索为临床应用活血化瘀药物防治冠心病做出了范式。 中医药与冠心病二级预防药物联合使用可改善冠心病患者的生活质量,且安全 性良好 [31] ,目前冠心病病证结合防治策略以活血化瘀为主,在此基础上衍生出 益气活血、行气活血、活血解毒等诸多治法,同时围绕其危险因素的防治,如 高血压 [123] 、高脂血症 [124] 及糖尿病 [125] 等皆有相应临床证据,不断促进精准诊疗 的实现。虽然目前糖尿病及血脂异常的中医药治疗已进入西医防治指南 [126-12 7] ,但多数中医药的应用场景较为模糊,对中医药与西药联合应用的具体策略、 获益与风险、应用周期等研究尚未有共识 [128] ,因此冠心病病证结合策略仍需不 断探索,定位关键优势环节仍是一大挑战。 5. 小结与展望 病证结合优化了现代中医药防治冠心病的研究模式,并成功确立了以血瘀 证与活血化瘀为主体的中西医结合治疗学发展方向 [129] ,活血化瘀防治心血管疾 病的理论创新与新药研究,是我国中西医结合领域六十余年来研究最为活跃、 成果最为突出的标志性成就之一,取得了一系列的创新性研究成果,在"血瘀 证"病证结合诊断标准的制定、 "活血化瘀"现代内涵的阐释、系列活血化瘀中 药新药的研发、临床疗效评价及作用机制探究等方面获得了丰厚成果,推动了 传统中医药的标准化和国际化进程,形成了高质量的临床转化应用证据 [30] ,为 冠心病的中医药防治做出了突出贡献。2011 年屠呦呦先生在 Nature Medicine 发表的文章中专门提及活血化瘀中药防治冠心病是来自中医药的智慧 [130] 。 病证结合中医药防治冠心病的临床转化研究需要不断进步,我们期望在以 下方向能够开展深入的研究。一是血瘀对早期血管衰老的识别、监测及早期干 预具有重要意义,需要积极发挥中医药"治未病"的优势,开展"因瘀致衰" [1 31] 及活血化瘀防治早期血管衰老的机制研究;二是随着代谢异常与心血管损害 之间因果关系的不断明确,代谢性心血管病的理念 [132][133] 不断得到学界公认, 心血管代谢风险的综合评估也越来越得到关注,研究糖脂代谢异常加重"血 瘀"促进冠心病发展的机制对于阐明血瘀证生物实质,丰富活血化瘀的治疗内 涵、拓展活血化瘀的应用范围意义重大;三是大数据技术与人工智能的快速发 展为冠心病的中西医结合诊疗方案或临床指南的优化研究提供了技术支撑 [134] , 如何利用人工智能技术加速冠心病临床指南的制订流程,提高效率,创新其传 播与实施模式,乃至改变指南的未来发展,已引起国内外学者的广泛关注 [135] ; 四是关注冠心病防治的老药新用研究,利用网络药理学等技术 [136] ,预测老药新 用的临床亮点开展系统化研究,对于缩短药物研发时间尽快服务于临床具有现 实意义。…”
Section: 血瘀证、活血化瘀与血小板功能unclassified